Cocaine-related acute aortic dissection: Patient demographics and clinical outcomes - Singh, Sarabjeet (Pulsus Group Inc, 2007)
BACKGROUND: To compare the demographics, inpatient mortality and short-term survival following hospital discharge between cocaine-using and non-cocaine-using patients presenting with acute aortic dissection. METHODS: Retrospective analysis of 46 consecutive patients admitted with the diagnosis of acute aortic dissection at the Mount Sinai Hospital (Chicago, USA) between 1996 and 2005. Among these 46 patients, cocaine use was temporally related to the presenting symptom in 13 patients (28%, group 1). Patients who were not cocaine users were grouped into group 2 (33 patients [72%]). RESULTS: Patients in group 1 were younger than those in group 2 (mean age 38±9 years versus 63±17 years, P=0.001), more likely to be smokers (13 of 13 patients [100%] versus 15 of 33 patients [45%], P=0.001) and had a higher prevalence of accelerated hypertension (mean blood pressure 210/130 mmHg) compared with group 2 (10 of 13 patients [77%] versus 11 of 33 patients [33%]) (P=0.01). Group 1 patients had a higher prevalence of type B dissection than group 2 (nine of 13 patients [69%] versus one of 33 patients [3%]). After hospital discharge, eight of 13 patients (62%) in the cocaine group continued to use cocaine. Mortality following hospital discharge was significantly higher in cocaine users (nine of 13 patients [69%]) compared with the non-cocaine users (four of 33 patients [12%], P=0.01). Recurrent dissection was the cause of death in five of the 13 deaths (42%) in the cocaine group. CONCLUSIONS: Patients presenting with acute aortic dissection temporally related to cocaine use are more likely to be younger, smokers, have higher prevalence of hypertensive crises, more likely to have type B aortic dissection and may have a higher mortality following hospital discharge, possibly due to continued cocaine use and recurrent aortic dissection.